Peningkatan Kesadaran Keamanan Siber melalui Edukasi Phishing dan Penipuan Digital bagi Siswa di Pekanbaru - Gunadi; Muhammad Jamaris; Susanti; Dewi Sari Wahyuni; T.Sy Eiva Fatdha (JCoos: Journal of Community Outreach in Science & Society, 2026)
The rapid advancement of digital technology has significantly enhanced convenience in daily activities. However, it has also increased the risk of cybercrime, particularly phishing and digital fraud. Students, as active users of the internet and social media, constitute a vulnerable group due to their limited awareness and understanding of cybersecurity practices. This community service initiative was designed to improve students’ awareness and knowledge of phishing threats, various forms of digital fraud, and effective preventive measures applicable in everyday contexts. The program was implemented through interactive outreach sessions, structured presentations, demonstrations of phishing case studies, guided discussions, and evaluations using pre-tests and post-tests to assess participants’ learning outcomes. The activity was held at a school in Pekanbaru City, with lecturers and university students serving as facilitators. The findings demonstrated a notable improvement in participants’ ability to recognize suspicious messages or links, understand the importance of safeguarding personal data, use strong passwords, implement two-factor authentication, and respond appropriately to potential digital fraud. Furthermore, participants exhibited high engagement during discussion sessions and were able to identify various forms of cybercrime commonly encountered in digital environments. This initiative is expected to strengthen digital literacy and enhance students’ preparedness to address cybersecurity challenges in the era of digital transformation.